2007
DOI: 10.1016/j.bmc.2006.10.036
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, antimalarial, antileishmanial, antimicrobial, cytotoxicity, and methemoglobin (MetHB) formation activities of new 8-quinolinamines

Abstract: We report the synthesis, in vitro antiprotozoal (against Plasmodium and Leishmania), antimicrobial, cytotoxicity (Vero and MetHb-producing properties) and in vivo antimalarial activities of two series of 8-quinolinamines. -[4-(4-ethyl-6methoxy-5-pentyloxy-8-quinolylamino)pentyl]-(2S/2R)-2-aminosubstitutedamides (51-63) were synthesized in six steps from 6-methoxy-8-nitroquinoline and 4-methoxy-2-nitro-5-pentyloxyaniline, respectively. Several analogs displayed promising antimalarial activity in vitro against P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
26
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(26 citation statements)
references
References 23 publications
0
26
0
Order By: Relevance
“…Such effect would be similar to what occurs with CQ, i.e., inhibition of heme crystallization through formation of a drug-heme complex, preventing clearance of hemeassociated toxicity from the parasite [166]. These were also presented by Jain et al studies involving several 8AQ compounds obtained by insertion of substituents at the quinolinic ring of PQ [167], where 4-ethyl-5-pentyloxyprimaquine has also displayed promising results [51]. Overall, it seems that insertion of an appropriate substituent at the quinoline's carbon 2 leads to a small improvement in antimalarial activity along with a decrease in general systemic toxicity.…”
Section: Modifications At the Quinoline Ringmentioning
confidence: 74%
See 2 more Smart Citations
“…Such effect would be similar to what occurs with CQ, i.e., inhibition of heme crystallization through formation of a drug-heme complex, preventing clearance of hemeassociated toxicity from the parasite [166]. These were also presented by Jain et al studies involving several 8AQ compounds obtained by insertion of substituents at the quinolinic ring of PQ [167], where 4-ethyl-5-pentyloxyprimaquine has also displayed promising results [51]. Overall, it seems that insertion of an appropriate substituent at the quinoline's carbon 2 leads to a small improvement in antimalarial activity along with a decrease in general systemic toxicity.…”
Section: Modifications At the Quinoline Ringmentioning
confidence: 74%
“…Some derivatives of PQ, especially 6-desmethyl-8-aminoquinolines, have been generally more active in vitro than the parent drug against macrophage-contained Leishmania [50]. Recently, Kaur et al presented several biological studies focused on 8AQs and confirmed that PQ has leishmanicidal activity in vitro, but with IC 50 values (w20 mg/mL) superior to those of reference drugs in leishmaniasis therapy, such as pentamidine (IC 50 ¼ 1 mg/mL) or amphotericin B (IC 50 ¼ 0.19 mg/mL) [51]. PQ also showed in vitro leishmanicidal properties when encapsulated in liposomes, against parasiteinfected macrophages [52].…”
Section: Against Leishmaniasismentioning
confidence: 99%
See 1 more Smart Citation
“…Primaquine (PQ) (compound 1 in Fig. 1), an antimalarial 8AQ, is known to exhibit activity against visceral leishmaniasis (3,12,13,15,25,29). Since it leads to some adverse side effects and has a lower therapeutic index than those of VL reference drugs, PQ currently has no applicability in the VL clinical setting.…”
mentioning
confidence: 99%
“…The antibacterial activity of 8-hydroxyquinoline and its derivatives is long-known. The drugs from this group are used as chemotherapeutics in medicine for more than 120 years (9,10,11,21), and in analytical chemistry as chelators (8,12). In previous studies of ours, some newly synthesized derivatives of 8-Quinolinol were shown to exhibit a higher microbiological activity (4,5,15).…”
Section: Introductionmentioning
confidence: 93%